Campus Infrastructure As A Strategic Resource for Enhancing Student Performance: Evidence From Universitas Majalengka - Rita Sri Silvia Pamuji; Alan Rusdiana; Denia Novitasari; Hani Laela Ramadani; Anisa Nurul Hidayah (Journal of Business and Behavioural Entrepreneurship, 2026)
This study aims to analyze the role of campus infrastructure in supporting student performance at Universitas Majalengka and to formulate strategic recommendations for infrastructure optimization based on students’ experiences and perceptions. The study employed a qualitative case study approach using deep interviews as the primary data collection technique. Fifteen students representing different faculties, academic levels, and disciplinary backgrounds were selected through purposive sampling. Data were analyzed using thematic analysis and source triangulation to identify recurring patterns, challenges, and priority needs related to campus infrastructure. The findings revealed that campus infrastructure influences student performance through three main mechanisms: facilitating access to learning resources, enhancing learning comfort, and supporting practical learning experiences. Internet connectivity emerged as the most frequently mentioned infrastructure component supporting students’ understanding of learning materials, followed by classroom facilities, air conditioning, laboratory facilities, learning technology, and library services. For academic productivity, laboratory facilities and internet access were identified as critical resources for completing assignments, conducting practical activities, and accessing academic information. The study also identified six development priorities: internet quality improvement, laboratory development, classroom enhancement, facility maintenance, infrastructure modernization, and equitable facility distribution across study programs. The proposed Campus Infrastructure Optimization Model suggests that digital, physical, practical, and supporting infrastructures collectively enhance academic engagement and student performance. The findings contribute to higher education infrastructure literature by positioning campus infrastructure as a strategic institutional resource influencing student success and educational quality.